Commensal Bacillus siamensis LF4 induces antimicrobial peptides expression via TLRs and NLRs signaling pathways in intestinal epithelial cells of Lateolabrax maculatus. Issue 134 (March 2023) - Liu, Zi-Yan; Yang, Hong-Ling; Wei, Cheng-Ye; Cai, Guo-He; Ye, Ji-Dan; Zhang, Chun-Xiao; Sun, Yun-Zhang
Abstract: Antimicrobial peptides (AMPs) play an important role in modulating intestinal microbiota, and our previous study showed that autochthonous Baccilus siamensis LF4 could shape the intestinal microbiota of spotted seabass ( Lateolabrax maculatus ). In the present study, a spotted seabass intestinal epithelial cells (IECs) model was used to investigate whether autochthonous B. siamensis LF4 could modulate the expression of AMPs in IECs. And then, the IECs were treated with active, heat-inactivated LF4 and its supernatant to illustrate their AMPs inducing effects and the possible signal transduction mechanisms. The results showed that after 3 h of incubation with 10 8 CFU/mL B. siamensis LF4, lactate dehydrogenase (LDH), glutamic oxaloacetic transaminase (GOT), glutamic propylic transaminase (GPT) activities in supernatant decreased significantly and obtained minimum values, while supernatant alkaline phosphatase (AKP) activity, β-defensin protein level and IECs Na + /K + -ATPase activity, AMPs (β-defensin, hepcidin-1, NK-lysin, piscidin-5) genes expression increased significantly and obtained maximum values ( P < 0.05). Further study demonstrated that the active, heat-inactivated LF4 and its supernatant treatments could effectively decrease the LDH, GOT, and GPT activities in IECs supernatant, increase AKP activity and β-defensin (except LF4 supernatant treatment) protein level in IECs supernatant and Na + /K + -ATPase and AMPs genes expression in IECs. Treatment with active and heat-inactivated B. siamensis LF4 resulted in significantly up-regulated the expressions of TLR1, TLR2, TLR3, TLR5, NOD1, NOD2, TIRAP, MyD88, IRAK1, IRAK4, TRAF6, TAB1, TAB2, ERK, JNK, p38, AP-1, IKKα, IKKβ and NF-κB genes. Treatment with B. siamensis LF4 supernatant also resulted in up-regulated these genes, but not the genes (ERK, JNK, p38, and AP-1) in MAPKs pathway. In summary, active, heat-inactivated and supernatant of B. siamensis LF4 can efficiently induce AMPs expression through activating the TLRs/NLRs-MyD88-dependent signaling, active and heat-inactivated LF4 activated both the downstream MAPKs and NF-κB pathways, while LF4 supernatant only activated NF-κB pathway. Highlights: Commensal B. siamensis LF4 effectively induces intestinal AMPs expression. B. siamensis LF4 induces AMPs expression through TLRs/NLRs-MyD88-dependent signaling and downstream MAPKs and NF-κB pathways. B. siamensis LF4 supernatant induces AMPs expression through NF-κB pathway, but not MAPKs pathway.